Review of literature on the productivity of public capital - Pellervo Hamalainen (Aboa Centre for Economics (ACE), 2009)
This paper summarizes previous results on the productivity of public capital. In recent literature, Aschauer's (1989) estimate for the productivity of public capital is often considered too high and the size of the effect is still open to debate. However, the positive effect of public capital on the productivity of the private sector is quite widely accepted.
Keywords: H11; H54; 330; Public capital; public investments; productivity